Predicting the likelihood and outcomes of continuous victimisation in the transition to adulthood - Böhle, Eva [Verfasser] (My University, 2025)
“Bullying can occur at all ages and has been associated with several negative impacts on the psychological and emotional well-being of victims. While the transition to adulthood may be an opportunity for victims to escape bullying, prior research has suggested some continuity of victimisation experiences into adulthood. However, research on victimisation among young adults remains scarce and no prior study has examined this issue in the Irish context. Binary logistic regression was used to examine the likelihood of victimisation at age 20 based on the respondent’s prior victimisation history and other risk factors, using data from 4693 respondents in the Growing Up in Ireland National Longitudinal Study at age 9, 13, 17 and 20. Moreover, the risk of depression and levels of global self-esteem at age 20 were examined in terms of (long-term) victimisation experiences. Respondents who were previously victimised in adolescence and respondents who were chronically victimised in childhood and adolescence were approximately 3.5 and 4 times more likely to be victimised at age 20 respectively than respondents who were never victimised. The negative outcomes of victimisation regarding the risk of depression and lower levels of self-esteem were more severe for respondents who experienced more persistent prior victimisation. In conclusion, more persistent long-term victimisation experiences are associated with more severe negative outcomes and an increased risk of continued victimisation throughout the transition to adulthood compared to less persistent or no prior victimisation. Therefore, supporting affected individuals to escape victimisation as early as possible is crucial.“ (author’s abstract; BIBB-Doku)

Der Übergang zum Erwachsensein ist eine wichtige und herausfordernde Phase auf dem Lebensweg junger Menschen. Jugendliche müssen beispielsweise Ablöseprozesse von ihrem Elternhaus bewältigen, Bildungs- und Berufsentscheidungen treffen und sich mit ihrer Identität und Weltanschauung auseinandersetzen. Diese Übergangsphase kann durch Mobbing-Erfahrungen erschwert werden, die mit verschiedenen negativen Auswirkungen auf das psychische und emotionale Wohlbefinden der Betroffenen in Verbindung gebracht werden. Gleichwohl kann für Jugendliche mit Mobbingerfahrung der Übergang zum Erwachsenenalter eine Gelegenheit sein, Mobbing aus Schulzeiten hinter sich zu lassen. Frühere Forschungsarbeiten deuten allerdings auf eine gewisse Kontinuität von Mobbingerfahrungen in der Kindheit und Jugend bis ins Erwachsenenalter hin. Der aktuelle Beitrag stellt evidenzbasierte Forschungsergebnisse und Einblicke in ein Forschungsfeld mit bisher großen Forschungslücken vor. Denn bislang ist der Forschungsstand zu Mobbing gerade unter jungen Erwachsenen noch als gering anzusehen. (BIBB-Doku)
Keywords: P 1.1 Jugendliche; G 1.3.2.2 Übergänge; G 2.4.2 Lebenskonzepte, -stile, Werte; 370; 300; Jugendlicher; Junger Erwachsener; Lebenswelt; Mobbing; Berufseinmündung